Nanophotonics Pioneer: Prof. Dr. Dieter Bimberg “Green Photonic Network: From VCSELs to Nanophotonics” - Jin-Wei Shi; Tien-Chang Lu; Fumio Koyama (Photonics, 2023)
We would like to celebrate Prof [...]